PELUKAAN ULANG SADAPAN PINUS DENGAN METODE BOR DI HUTAN PENDIDIKAN GUNUNG WALAT: Re-Tapping Pine Resin Using the Drilling Method in Gunung Walat University Forest (Jurnal ForestrIndo, 2025)
Re-tapping is carried out to utilize tapping holes that have healed, allowing the same spot to be used again without continuously creating new wounds on the tree.   This study explains effect of re-tapping pine sap tapping holes using a drill method, comparing the productivity of sap between new tapping holes and recovered holes, and determining the optimal drill bit size. The treatments applied were the type of hole (new and recovered) and the use of four drill bit sizes (5/8, 6/8, 7/8, and 8/8 inches). Resin productivity data were analyzed using the Mann-Whitney U test and the Kruskal-Wallis test. The results showed that re-tapping on recovered holes could still produce resin, but the productivity was not as high as that of new holes. The larger the drill bit size, the more latex produced. The 8/8-inch drill bit size yielded the highest productivity, but the 6/8-inch size produced pine resin that was not significantly different from the 7/8-inch and 8/8-inch sizes. The use of a 6/8-inch drill bit is recommended as the optimal choice to support sustainable pine resin production with minimal damage, allowing the tapping wounds to heal more quickly.